2001
DOI: 10.1037/0021-843x.110.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Current and lifetime comorbidity of the DSM-IV anxiety and mood disorders in a large clinical sample.

Abstract: The comorbidity of current and lifetime DSM-IV anxiety and mood disorders was examined in 1,127 outpatients who were assessed with the Anxiety Disorders Interview Schedule for DSM-IV: Lifetime version (ADIS-IV-L). The current and lifetime prevalence of additional Axis I disorders in principal anxiety and mood disorders was found to be 57% and 81%, respectively. The principal diagnostic categories associated with the highest comorbidity rates were mood disorders, posttraumatic stress disorder (PTSD), and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
833
5
33

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,256 publications
(917 citation statements)
references
References 39 publications
46
833
5
33
Order By: Relevance
“…For example, Segerstrom, Stanton, Alden, & Shortridge (2003) found that negative affectivity is generated by negative thinking of any type; Chelminski & Zimmerman (2003) found that worry occurs in depression; and Nolen-Hoeksema (2000) found that rumination predicts the onset of anxiety. These findings suggest a shared component to these forms of repetitive thinking and a considerable research base supports this showing that anxiety and depression are frequently comorbid (Brown & Barlow, 1992;Brown, Campbell, Lehman, Grisham, & Mancill, 2001;Kessler et al, 1994;Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995;Kessler et al, 1998). This comorbidity may be explained in a number of ways: firstly, it is possible that having one disorder increases the risk of developing another; alternatively, it is possible that anxiety and mood disorders may develop from the same underlying predisposition (Barlow, 2002).…”
Section: The Link Between Rumination and Worrymentioning
confidence: 95%
“…For example, Segerstrom, Stanton, Alden, & Shortridge (2003) found that negative affectivity is generated by negative thinking of any type; Chelminski & Zimmerman (2003) found that worry occurs in depression; and Nolen-Hoeksema (2000) found that rumination predicts the onset of anxiety. These findings suggest a shared component to these forms of repetitive thinking and a considerable research base supports this showing that anxiety and depression are frequently comorbid (Brown & Barlow, 1992;Brown, Campbell, Lehman, Grisham, & Mancill, 2001;Kessler et al, 1994;Kessler, Sonnega, Bromet, Hughes, & Nelson, 1995;Kessler et al, 1998). This comorbidity may be explained in a number of ways: firstly, it is possible that having one disorder increases the risk of developing another; alternatively, it is possible that anxiety and mood disorders may develop from the same underlying predisposition (Barlow, 2002).…”
Section: The Link Between Rumination and Worrymentioning
confidence: 95%
“…Comorbidity is associated with greater severity of depressive symptoms, and lower treatment response rates (Young, Mufson, & Davies, 2006), alongside greater social and occupational impairment (Ansseau et al, 2008). The association with depression is particularly strong for post-traumatic stress disorder, generalized anxiety disorder, obsessive-compulsive disorder, and social phobia (Brown, Campbell, Lehman, Grisham, & Mancill, 2001). The Zurich study notes higher prevalence of depression and panic disorder reporting that 12% of their sample displayed comorbidity (Volirath & Angst, 1989).…”
Section: Accepted M Manuscript Prevmentioning
confidence: 99%
“…Psychiatric epidemiology studies suggest that similar solutions would be found in some, but not all, mental disorders with the determining factor being the degree of heterogeneity and breadth of comorbidity associated with the index disorder. Of the anxiety disorders, PTSD shows the most severe and diverse pattern of diagnostic comorbidity (Brown, Campbell, Lehman, Grisham, & Mancill, 2001), with frequently co-occurring conditions ranging from those of the internalizing spectrum, including the unipolar mood and anxiety disorders, to the externalizing spectrum, such as antisociality and substance abuse. Certain other disorders show similar patterns of comorbidity spanning these spectra.…”
Section: Study Limitations and Directions For Future Researchmentioning
confidence: 99%